Cylas formicarius invation and its impact on sweet potato productivity in Wamena, Papua Pegunungan - Inrianti, Inrianti; Tulak, Alber; Mosip, Erinus; Pumoko, Patras (Universitas Muhammadiyah Mataram, 2025)
Sweet potato (Ipomoea batatas L.) is a staple food commodity in Wamena, Papua Highlands, yet its productivity has declined due to pest infestations. This study aimed to identify the infestation of Cylas formicarius (sweet potato weevil) and analyze its impact on yield quality and quantity. Field surveys were conducted using a cross-sectional observational design, morphological identification of pests, and descriptive analysis of leaf, stem, and tuber damage. Results revealed that C. formicarius was the predominant pest, characterized by leaf perforations, stem cracks, and decayed tubers containing larvae. Such damage significantly reduced harvest quality and quantity, rendering tubers unsuitable for consumption and storage. The discussion highlights that humid environmental conditions and traditional farming practices increase infestation risks. In conclusion, C. formicarius poses a serious threat to sustainable sweet potato production in Wamena, thus requiring urgent ecological interventions. Recommended strategies include implementing ecologically based integrated pest management, such as crop rotation, the use of local botanical insecticides, pheromone traps, and farmer education.